The ADP-ribose reactive NUDIX hydrolase isoforms can modulate HIF-1 alpha in cancer cells - Yoon, Byungboon; Yang, Eun Gyeong; Kim, So Yeon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
The human nucleoside-diphosphate linked moiety-X (NUDIX) hydrolases that utilize ADP-ribose and NADH/NAD(+) are overexpressed in cancer cells, but their roles in hypoxia inducible factor-1 alpha (HIF-1 alpha) regulation have not yet been revealed. Here, we showed that these NUDIX hydrolases negatively regulated HIF-1 alpha, accumulation by modulating the Ca2+ dependent AMP-activated protein kinase (AMPK) signaling pathway. In specific, knockdown of NUDT9 resulted in accumulation of free ADP-ribose that triggered Ca2+ influx mediated by transient receptor potential cation channel subfamily M member 2 and subsequent activation of Ca2+/calmodulin-dependent protein kinase kinase beta (CaMKK beta). In addition, AMPK activation by CaMKK beta was shown to enhance HIF-1 alpha accumulation. Our findings provide insights into the action of NUDIX hydrolases as an additional, discrete modulator of HIF-1 alpha accumulation. (C) 2018 Published by Elsevier Inc.
Keywords: ACTIVATED PROTEIN-KINASE; OXIDATIVE STRESS; MESSENGER-RNA; CHANNEL TRPM2; OVEREXPRESSION; MITOCHONDRIA; MECHANISMS; GROWTH; HIF